Lightweight Design and Optimization Effect Evaluation of Hydro Generator Set - Liao, Yongyi; Liao, Baiyu (Manufacturing Technology Journal, 2021)
With the increase of hydro generators capacity and unit size, the requirement of lightweight is prominent. Taking a mixed-flow hydro generator as the research objects, the strength, the stiffness and the dynamic characteristics of upper bracket, stator frame, lower bracket and head cover have been simulated and analyzed by means of establishing their finite element models. Based on sizing optimization design method, plate thicknesses of the main parts were selected as the design variables, and strength and stiffness were taken as the constraint conditions to optimize them with the minimum mass as the objective function. Through lightweight optimization design, the maximum normal stress and maximum displacement of the optimized main parts are within the allowable value range, modal analysis shows that their dynamic characteristics meet the requirements. The lightweight optimization design reduced the weight of hydro generator by 3457kg in total. Optimization effect evaluation under full load operation and site test between the original and improved hydro generator set show that the dynamic characteristics are improved and the performances meet the design requirements.
Keywords: Hydro generator set; Lightweight optimization design; Sizing optimization; Structural improvement